Metabolic remodeling and cardiac dysfunction in left ventricular noncompaction: Insights from the MYH7 Q315R model - Shinya Takarada; Yukiko Hata; Keisuke Yaku; Hironori Izumi; Kazuki Fujii; Masaaki Omura; Ichiro Takasaki; Kaori Tsuboi; Mako Okabe; Nariaki Miyao; Hideyuki Nakaoka; Keijiro Ibuki; et al. (PLoS ONE, 2025)
Left ventricular noncompaction (LVNC) is a form of cardiomyopathy characterized by excessive trabeculation and a thin compacted myocardial layer. Variants in MYH7 , which encodes the β-myosin heavy chain, are among the most commonly identified genetic causes of LVNC. Despite its clinical relevance, the metabolic disturbances associated with LVNC remain poorly understood, and the pathophysiological mechanisms have not been investigated in an animal model of MYH7 -related LVNC. To address this gap, we generated a mouse model carrying the human MYH7 Gln315Arg (Q315R) variant, a representative mutation linked to LVNC. Mice with the MYH7 Q315R variant exhibited key features of LVNC, including impaired diastolic function, reduced contractility, and excessive trabeculations extending across the ventricular walls. Metabolomic analysis revealed significant metabolic remodeling, characterized by suppressed glycolysis, lipid oxidation, and tricarboxylic acid (TCA) cycle activity. Levels of key intermediates, including glucose-6-phosphate, pyruvate, and acetyl-CoA, were reduced, along with downregulated expression of glycolytic and mitochondrial genes. Additionally, alterations in the pentose phosphate pathway indicated impaired nucleic acid synthesis, while an increased lactate-to-pyruvate ratio suggested a metabolic shift toward anaerobic glycolysis. This study underscores the critical role of metabolic inflexibility—marked by suppression of glycolysis, lipid metabolism, and TCA cycle activity—in the pathophysiology of LVNC. Targeting these dysregulated metabolic pathways, particularly by enhancing mitochondrial function and restoring metabolic adaptability, presents a potential therapeutic strategy for LVNC treatment.